The human dimension of information security: Analysis of social engineering techniques used in security awareness auditing using the SPEAKING model (Academic Journal of Internal Affairs, 2018)
The author provides an overview of how hacker sub-culture and criminal organizations intertwine, and social engineering in the field of communication.
Keywords: information security; SPEAKING model; security awareness